Individual profiles and wine consumption patterns in Tenerife [Canary Islands, Spain]. A multinomial logit model - Rodríguez Donate, M.C.; Cáceres Hernández, J.J.; Guirao Pérez, G.; Cano Fernández, V.J. (Spanish Journal of Agricultural Research, 2009)
The aim of this study is to analyze the decisions on the frequency of wine consumption to detect the individual characteristics of the potential consumer that influence the propensity towards each decision. Discrete choice models, and in particular, logit models have been seen as tools which are able to identify the way in which a specific combination of characteristics that define the residents of Tenerife conditions his decision on consumption frequency. In general, a regular consumption is not usual for women, which only do so occasionally. On the other hand, the ratio of occasional consumption probability to high frequency consumption probability falls as the age increases. In this sense, the identification of the combinations of individual characteristics associated with patterns of extreme consumption clearly indicates that women and young people are the two consumer segments which should be objects of specific marketing strategies. Any case, the design of such strategies requires investigating about individual preferences and goes beyond the scope of this paper.